The constitutional politics of socio-economic rights: proceduralism ‘writ large’ - Smilov, D (Foundation for Law, Justice and Society, 2008)
This policy brief examines the constitutional protection of socio-economic rights in their relationship to the political process. How should constitutional courts approach claims of socio-economic rights? Should they defer to politically elected bodies? If not, what kind of arguments should judges employ in their reasoning?